THE EFFECT OF DUOLINGO USAGE ON STUDENTS’ VOCABULARY MASTERY OF SEVENTH-GRADE STUDENTS AT MTs PAB 1 HELVETIA - Nurbaiti Ali (Jurnal Serunai Bahasa Inggris, 2021)
Due to Covid-19 pandemic, most of teaching learning process was not conducted at class. The teacher and students had the teaching learning process via online on the internet. This situation occurred serious problem for the students related to the teaching learning goals. Most of students found more difficulties in learning English. Less interactions at class made their vocabulary knowledge and ability became low. They had no chance to explore their vocabulary. In fact, they were difficult to mention some vocabularies around them. They also felt difficult to share their opinion by using English. This research aimed to know the difference, increase or improvement and effect of Duolingo usage on students’ vocabulary mastery. This research was a quantitative approach. The research location was at MTs PAB 1 Helvetia on Jl. Veteran Pasar IV Helvetia with sixty students as the sample. The sample was divided into Experimental and Control group. The Experimental group was taught vocabulary by using Duolingo while the Control group was taught vocabulary by common method. The students’ score result was the primer data and analyzed by using T-Test formula. The calcualtion used SPSS (Statistical Package for Social Science) 20.0 to count the data as valid as it was. The research finding proved that there was a significance difference, increase or improvement and effect of Duolingo usage on students vocabulary mastery. Duolingo usage affected students’ vocabulary mastery of the seventh-grade students at MTs PAB 1 Helvetia. Keywords : Duolingo, Vocabulary Mastery